2021
DOI: 10.1186/s12943-021-01468-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel CTNNB1 mutation in Craniopharyngioma by whole-genome sequencing

Abstract: Background Craniopharyngioma (CP) is rare histologically benign but clinically challenging tumor because of its intimate relationship with the critical structure in the central brain. CP can be divided into two major histologic subtypes: adamantinomatous-type CP (ACP) and papillary-type CP (PCP). Although some genetic aberrations for both categories have been revealed in previous studies, the complete spectrum of genetic changes of this tumor remains unknown. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…The latest study has confirmed that β-catenin nuclear stability activates the wnt-signaling pathway and promotes cell proliferation 41 . Our study also confirmed that the cyst wall has more β-catenin nuclear positive cells than the solid body, indicating that the cyst wall has a stronger proliferative capacity.…”
Section: Discussionmentioning
confidence: 98%
“…The latest study has confirmed that β-catenin nuclear stability activates the wnt-signaling pathway and promotes cell proliferation 41 . Our study also confirmed that the cyst wall has more β-catenin nuclear positive cells than the solid body, indicating that the cyst wall has a stronger proliferative capacity.…”
Section: Discussionmentioning
confidence: 98%
“…The Wnt signaling pathway is an important aspect of ACP pathogenesis. CTNNB1 -Mut has been shown to promote ACP primary cell proliferation by activating Wnt/β-catenin signaling ( 22 ). On the other hand, reducing the expression of β-catenin can significantly inhibit the proliferation of ACP cells, and β-catenin can promote the expression of Fascin mRNA and Fascin by acting on Fascin genes in the nucleus, thus promoting the migration and invasion ability of ACP cells ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our previous studies also investigated essential transcript factor (TF)–lncRNA pairs based on an integrated algorithm, which provided new insights into the underlying mechanism of ACP development ( 8 ). Currently, the accumulation of beta-catenin caused by CTNNB1 mutations has been recognized as the driver mutations in ACPs ( 9 11 ). Studies focusing on the murine ACP model raised a new hypothesis in initiating tumor formation: tumors derived from SOX2− cells transformed by SOX2+ pituitary stem cells expressing beta-catenin in the senescence-associated secretory phenotype (SASP) ( 12 ).…”
Section: Introductionmentioning
confidence: 99%